New designs for archaeological reports - Rahtz, S; Carr, L; Hall, W (George Street Press, 1990)
Presents a system being developed ('Lace') to assist archaeological publication. The aim is to 'combine support for linear, but structured, narrative; traditional database technology to handle large volumes of data; the ability to mix media; and the freedom for the reader to switch seamlessly between following the writer's flow of thought, and trying to investigate the data in an unbiased way.' Lace is a hypertext front end to documents which incorporates: the LaTeX system for creating text; NeWS, a PostScript-based windowing display system; and a document library server to manage the text and other media such as pictures. Lace regards each document as a structured collection of nodes such that any document can link with any other document via the nodes.